Optimal selection of the nutritive value - Petkus , Tomas; Dzemyda, Gintautas (Lietuvos matematikos rinkinys, 1998)
The methodology of feed optimization allows the price decrease and improves the nutritive value. The metodology includes a formal problem statement, interactive selection of parameters of the optimized function and application of the algorithms of non-linear programming. The method enables us to get the optimal values of the objective function argument with the best parameters of the function, according to the planners.